2018
DOI: 10.3390/su10114145
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Recovery of CO2 by Using Visible-Light-Responsive Crystal Cuprous Oxide/Reduced Graphene Oxide

Abstract: A simple solution-chemistry method has been investigated to prepare crystal cuprous oxide (Cu 2 O) incorporated with reduced graphene oxide (designated as Cu 2 O-rGO-x, where x represents the contents of rGO = 1%, 5% and 10%) in this work. These Cu 2 O-rGO-x composites combine the prospective advantages of rhombic dodecahedra Cu 2 O together with rGO nanosheets which have been studied as visible-light-sensitive catalysts for the photocatalytic production of methanol from CO 2 . Among the Cu 2 O-rGO-x photocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Thus Cu 2 O can absorb visible light at a wavelength of about 400-800 nanometers along with the excitation of electron-hole pair. And it has been widely investigated for photocatalyst reaction under visible light irradiation [21][22][23]31]. Thus Cu 2 O is considered to be a promising visible light active photocatalyst to produce graphene [23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus Cu 2 O can absorb visible light at a wavelength of about 400-800 nanometers along with the excitation of electron-hole pair. And it has been widely investigated for photocatalyst reaction under visible light irradiation [21][22][23]31]. Thus Cu 2 O is considered to be a promising visible light active photocatalyst to produce graphene [23].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Cu 2 O (Cu I ) micro-and nanocrystals have a wide variety of different structures with well-defined morphologies like cubes, rhombic dodecahedral, octahedron, concave cube, sphere, stars, etc. [15][16][17][18]. It has been reported that Cu 2 O nanocubes were successfully employed in the crosscoupling reaction of aryl halides and phenols [19].…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalysts demonstrated higher photo-activity than TiO2 in most cases especially under visible light irradiations. Most of these VLR photocatalysts are metal/non-metal oxides such as WO3, NiO2, In2O3 TaO4, Fe2O3, Bi2O3 etc [33]. Although VLR photocatalysts have reported higher photo-activity and product yield compared to UV sensitive TiO2, selecting/highlighting a material as the best is not accurate as most reported works are carried out under varying reaction and experimental conditions.…”
Section: Introductionmentioning
confidence: 99%